HaNDL with bilateral central venous occlusions. Issue 1 (2nd June 2020) - Wang, Wendy; Mack, Heather G; Stawell, Richard; White, Owen; Waterston, John
Abstract : Background: The syndrome of Headache and focal Neurological Deficits with cerebrospinal fluid Lymphocytosis (HaNDL) is considered a rare, idiopathic and self-limited condition. Methods: We present a patient with HaNDL who had unique findings of florid optic disc haemorrhages from bilateral central retinal vein occlusions. Results: Our patient made a full recovery with conservative management. Conclusion: It is important for medical attendants to recognise that HaNDL syndrome can be associated with neuro-ophthalmic complications.